ОТ КОНТРАСТИВНЫХ ДО СОЦИОЛИНГВИСТИЧЕСКИХ ИССЛЕДОВАНИЙ ХОРВАТСКОГО И СЛОВЕНСКОГО ЯЗЫКОВ (Филолошки студии, 2019)
The paper presents the contrastive socio-linguistic studies and projects of the Croatian and foreign languages, notably of Croatian and Slovene, the two neighboring and related languages. Some examples illustrate how the results of these studies are applied in the teaching of Croatian in Slovenian languages. (1) Teaching Croatian is unconceivable without the contrastive approach at the university level as well – all language courses, textbooks, monographs; different contrastive projects, etc. are based on the contrastive principle. (2) The results were used in preparing the curriculum for Croatian as an elective subject in Slovenian nine-year elementary schools (grades 7, 8 and 9), in preparing didactic sources and in the continual education programs for teachers. (3) Results of contrastive studies are also applied in other forms of advanced education, such as seminars for court interpreters, translators, for exams of Croatian as a foreign language, etc. It can be concluded that contrastive analyses, as well as error analyses and didactic sources based on them will continue to play a significant role in language teaching, particularly teaching of related languages; this is actually the only way in which the most persistent types of mistakes can be pre-empted and eliminated at all language / speech levels.